La production animale au Mali central - Wilson, R.T. (1982)
Summarizes a baseline study of the traditional livestock production system of central Mali, classifying production systems in the study in the study zone according to the degree of dependence on livestock products for gross revenue or food supply of the household or production unit, and according to types of agriculture associated w. livestock. Describes primary resources available for livestock production; livestock numbers & movement patterns; the agropastoral system; and the pastoral system associated w. rice cultivation in the Niger innundation zone.